The origins of courtliness : civilizing trends and the formation of courtly ideals, 939-1210 - Jaeger, C. Stephen (Middle Ages series., 1985)
Selected by Choice magazine as an Outstanding Academic BookArgues that the origins of courtliness lie in the German courts, their courtier class, and the education for court service in the tenth and eleventh centuries.